Development of intelligent halochromic packaging films based on zein and pH-sensitive enocyanins for evaluating the fish freshness - Llinares Verdu, A. (2025)
This work reports on the development of halochromic pH-sensitive films based on zein, glycerol and enocyanin extract. Enocyanins improve the mechanical properties of the zein films, increasing tensile strength from 6.8 to 13.9 MPa. Thermal stability of zein films was not affected by the addition of enocyanins, with a maximum degradation rate temperature of 330–345 ºC. All films present certain capacity to change their color with pH. Films were exposed to ammonia and their color changed from brownish to green-blue colors, indicating pH- variation. In-vivo tests with hake fish demonstrate that after 8 days of exposure, when the fish become spoiled, films change their color to green-blue tonalities as a result of a more alkaline pH environment. Total color change is more pronounced in the films with higher composition of enocyanins, proving their great applicability in the food industry as freshness non-destructive and non-toxic indicators. Enocyanins increased the affinity of the films for water up to a point, with a minimum contact angle of 29.5º. Films were transparent and FTIR measurements suggested that enocyanins form strong hydrogen bonds with zein.